(untitled) (Global Journal of Human-Social Science, 2023)
Electronic literature or hypertext fiction as a new trend in the development of literary works demonstrates ever-lasting inexhaustible search for new ways of self-expression by human mind which goes along with investigations and exploitations of new possibilities modern technologies provide for composition of works of fiction that belong to the age-old literary genres The structure of a hypertext provides a way to link and get access to multiple parts of a text that are joined by various types of relations as a web of nodes By choosing a certain link from an available number of options a reader makes a leap in time and consequently in space that is changes what M Bakhtin defined as a chronotope – a constitutive unit of form and content in literature that combines spatial and temporal parameters into one whole into a system of coordinates for a certain narrative action A linked structure of a hypertext organized into a network of fragments and connections between them forms a mosaic of chronotopes A change of time dimension entails a change of space dimension and results in constant change of chronotopes creating the effect of a kaleidoscope each turn of which forms a new picture from available parts